A study on the corporate image of zakat institutions - Siti Ngayesah binti Ab.Hamid (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
The privatisation of several zakat institutions in Malaysia has opened a new phase in zakat administration, especially through the introduction and implementation of corporate values, with the aim of improving institutional image. Various activities and promotional efforts have been done in order to achieve this objective. These efforts involve a significant amount of spending and would become a waste if it fails to achieve the intended goals. Therefore, this study was conducted to identify the factors that determine the image of zakat institutions among zakat contributors and non-contributors. Based on the theory that the basic component of corporate image consist of emotional and functional components, four factors were proposed, which are reputation, corporate communication, access to service and contact personnel. 225 questionnaires were collected and analysed using multiple regression analysis. A 5-point Likert-type scale was used to measure the corporate image of zakat institutions. Findings reveal that reputation and contact personnel have a significant relationship with image. Corporate communication and access to service shows a positive relationship with image, but the relationship was not statistically significant. The findings nevertheless have broadened understanding of the concept of image and its antecedent in the context of zakat institutions in Malaysia.